Initiation and Development of Wetlands in Southern Florida Karst Landscape Associated With Accumulation of Organic Matter and Vegetation Evolution. Issue 6 (26th June 2019) - Zhang, Xiaowen; Bianchi, Thomas S.; Cohen, Matthew J.; Martin, Jonathan B.; Quintero, Carlos J.; Brown, Amy L.; Ares, Angelica M.; Heffernan, James B.; Ward, Nicholas; Osborne, Todd Z.; Shields, Michael R.; Kenney, William F.
Abstract: Biological processes exert important controls on geomorphic evolution of karst landscapes because carbonate mineral dissolution can be augmented and spatially focused by production of CO2 and biogenic acids from organic matter (OM) decomposition. In Big Cypress National Preserve in southwest Florida, depressional wetlands (called cypress domes) dissolved into surface‐exposed carbonate rocks and exhibit regular patterning (size, depth, and spacing) within the pine upland mosaic. To understand when wetland basins began to form and the role of spatially varying OM decomposition on bedrock weathering, we constructed age profiles of sediment accretion using compound‐specific radiocarbon analysis of long‐chain fatty acids and measured bulk OM properties and biomarker proxies (fatty acids and lignin phenols) in different zones (center vs. edge) of the wetlands. Based on compound‐specific radiocarbon analysis, landscape patterning likely began in the middle to late Holocene, with wetlands beginning to form earlier at higher elevations than at lower elevations within the regional landscape. Dominant vegetation appears to have shifted from graminoids to woody plants around 3, 000 calendar years before the present, as reflected in downcore bulk carbon isotope data and lignin concentration, likely from increased precipitation and hydroperiods. OM is mostly accumulated in wetland centers, and wetland centers exhibit more carbonate dissolution due to inundation limiting atmospheric ventilation of CO2 . Landscape development and patterning thus arise from interactions between hydrology, ecology, and ecological community evolution that control carbonate mineral dissolution. Key Points: Regularly patterned depressional wetlands in southwest Florida were likely developed in the middle to late Holocene Wetland vegetation likely shifted from graminoids to woody plants as a result of precipitation change and concomitant hydroperiods Decomposition of soil organic matter appears to be more efficient at bedrock weathering in wetland centers than edges